Effect of potassium on growth and yield of patchouli [Pogostemon cablin (Blanco) Benth.] - Singh, M (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted for two years to study the influence of amount and method of potassium (K) application on growth, herbage yield, oil yield and potassium uptake of patchouli in a semi-arid tropical climate. The results revealed that application of 41.5 kg K ha-1 produced significantly higher plant height, plant spread, herbage and oil yield over control (no fertilizer). The increase in herbage yield, oil yield and K uptake was 118.8%, 52.8% and 18.8% higher, respectively over control. Application of potassium in two splits (½ basal + ½ after 60 days) also significantly increased plant height, plant spread, and increased the herbage yield, oil yield and K uptake by 32.2%, 37.9% and 33.2%, respectively over basal application. Oil content was not influenced by amount and method of K application.